Understanding regulations, tax sanctions and taxpayer compliance: the role of risk preference moderation - Egha Nurwati; Umaimah Umaimah (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to provide empirical evidence empirical evidence related to tax knowledge and tax sanctions with risk preference as moderating preference as a moderator for increasing taxpayer compliance. Methodology/approach: The population of this study were taxpayers registered at KPP Pratama Gresik, and the technique used for sample testing was purposive sampling. The research data was collected by distributing questionnaires and analyzed using the Smart-PLS software application. Findings: The results of Understanding Tax Regulations have a positive effect on taxpayer compliance while Tax Sanctions have no positive effect on taxpayer compliance, as well as risk preferences that cannot moderate the understanding of tax regulations and tax sanctions on taxpayer compliance. Practical and Theoretical contribution/Originality: This study can explain the Planned Behavior theory and Prospect Theory regarding the behavior of a taxpayer at the level of taxpayer compliance. This study also provides an overview of the level of compliance of individual taxpayers. Research Limitation: The limitations in this study are limited time and limited resources to collect data within a certain period. In addition, data collection that only relies on surveys has the potential to affect the representativeness of the findings, because only some taxpayers are willing to participate. Limited access to tax data. Future research is recommended to extend the period of data collection to obtain more representative results and consider using other methods that can overcome limitations in data collection, such as the use of broader secondary data.